2022
DOI: 10.3390/polym14102033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thermoplastic Polyurethanes Containing Bio-Based Polyester Polyol and Their Fiber Property

Abstract: Among the starting materials of thermoplastic polyurethanes (TPUs), it was confirmed that succinic acid-based polyester biopolyols having different molecular weights (Mn = 1000, 2000, and 4000) affect the physicochemical properties of the final polymer significantly. Bio-TPUs synthesized through a solvent-free one-shot polymerization process were synthesized with a polyester polyol, 1,4 butanediol (BDO), and 4,4′-methylene diphenyl diisocyanate (MDI) in a molar ratio of 1:1:2. As a control group, one typical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Additionally, NCO peaks were observed around 2270 cm −1 in the PHDE spectrum, albeit with reduced intensity compared to HMDI, indicating a reaction between a few NCO groups in HMDI and DMEA. However, the characteristic NCO peaks disappeared in the FTIR spectrum of HUDM, suggesting the reaction of the remaining isocyanate groups in HMDI with urushiol [28]. Furthermore, a series of characteristic absorption peaks corresponding to the phenolic amide ester linkages were observed, confirming the successful coupling of NCO and OH groups.…”
Section: Synthesis and Structural Characterization Of The Hudm-sb And...mentioning
confidence: 92%
“…Additionally, NCO peaks were observed around 2270 cm −1 in the PHDE spectrum, albeit with reduced intensity compared to HMDI, indicating a reaction between a few NCO groups in HMDI and DMEA. However, the characteristic NCO peaks disappeared in the FTIR spectrum of HUDM, suggesting the reaction of the remaining isocyanate groups in HMDI with urushiol [28]. Furthermore, a series of characteristic absorption peaks corresponding to the phenolic amide ester linkages were observed, confirming the successful coupling of NCO and OH groups.…”
Section: Synthesis and Structural Characterization Of The Hudm-sb And...mentioning
confidence: 92%
“…Gel permeation chromatography (GPC) analysis was performed through Ecosec GPC (Tosoh Company, Tokyo, Japan) to measure the number average molecular weight (M n ), weight average molecular weight (M w ), and polydispersity index (PDI) of the TPU samples. The sample solution for analysis was prepared by adding 50 mg of dried polymer to 5 mL of inhibitor-free tetrahydrofuran solution, completely dissolving it at room temperature for one day, and then filtering it with a 0.45 µm PTFE filter [35]. The HS content of the TPU samples was calculated as a percentage of the mass of the chain extender and isocyanate making up the HS out of the total mass of all starting materials [36].…”
Section: Characterizationmentioning
confidence: 99%
“…Various new methods have been developed for synthesizing different types of polyester polyols with unique structures. These include Jatropha-Oil-Based Polyester Polyol 33 , Polyester Polyol from Cyclohexanone plant wash water 34 , isosorbide-based polyester polyols 35 , polyester polyol from Direct conversion of waste polyesters 36 , polyester polyol based on epoxidized soybean oil 37 , and other works reported in the literature [38][39][40] . Recent investigations on polyurethane have revealed that vegetable oil fatty acids can serve as a suitable replacement for petroleum-based raw materials [41][42][43] .…”
Section: Introductionmentioning
confidence: 99%